Mathematical models for describing growth in peach (Prunus persica [L.] Batsch.) fruit cv. Dorado (2021)
Among deciduous species, the peach tree (Prunus persica [L.] Batsch.) is of great importance in the high tropics. However, the growth behavior of this fruit for different cultivated varieties is unknown. So, adjustment to double sigmoid curves is assumed for all even though sigmoid type curves have been reported for many peach cultivar. This has led to the misinterpretation of information, impeding decision-making in terms of management. Non-linear regression models best describe the growth curves, where parameters are estimated by minimizing the sum of squares of the errors. In particular, the logistic model is one of the better options for correctly representing fruit growth. Therefore, the objective of this research was to determine the efficiency of mathematical models for describing growth in P. persica cv. Dorado fruits grown under conditions in the municipality of Tuta-Boyaca. The Logistic model was the most appropriate for describing the growth curves based on fresh or dry weight, while the Gompertz model was the most suitable for describing the polar and equatorial diameters of the Dorado variety fruits because they were used to generate these parameters with practical interpretations and they adequately represented the biological process.